Chris Hani - Macmillan, Hugh, 1945- (Book collections on Project MUSE., 2021)
Chris Hani was one of the most highly respected leaders of the African National Congress, the South African Communist Party, and uMkhonto we Sizwe. His assassination in 1993 threatened to upset the transition to democracy but also prompted an intervention by Nelson Mandela, which accelerated the process.